Correlating vaccination status of confirmed African horse sickness cases with disease outcome in South Africa - Crafford, Jan Ernst (University of Pretoria, 2022)
Dissertation (MSc (Veterinary Science Tropical Diseases))--University of Pretoria, 2020.